Safety and Efficacy of Keratorefractive Lenticule Extraction (KLEx) for High Myopia with the CLEAR Platform - Matteo Posarelli; Lorenzo Azzaro; Stefania V. Fields; Tara Moore; Antonio Leccisotti (Journal of Clinical Medicine, 2026)
Objectives: To assess the safety and efficacy of Keratorefractive Lenticule Extraction (KLEx) in patients with myopia ≥ 5 diopters (D). Methods: Retrospective study of KLEx procedures performed at Siena Eye Laser (Poggibonsi, Italy) with the CLEAR platform of the Ziemer Z8 femtosecond laser. Results: We included 137 eyes of 85 patients; mean age was 33.8 ± 8.3 years. Assessment at baseline showed a mean myopic error of −7.3 ± 1.4 D, a mean astigmatic error of 1.1 ± 0.8 D, and a mean spherical equivalent (SE) of −7.8 ± 1.6 D. Preoperative corrected distance visual acuity (CDVA) was 0.0 logMAR or better in all eyes. Mean corneal thickness was 510.0 ± 26.9 µm. At post-operative day 1 (POD1) uncorrected distance visual acuity (UDVA) was 0.1 ± 0.1 logMAR, with a mean residual SEQ of 0.1 ± 0.8 D. At 6 months follow-up, mean UDVA significantly increased to 0.0 ± 0.0 logMAR (p < 0.001), with a mean residual SE of −0.12 ± 0.7 D (p > 0.05 compared to POD1). At 24 months, the mean UDVA remained stable at 0.0 ± 0.0 logMAR, with a mean residual SE of −0.1 ± 0.4 D as manifest refraction (all p > 0.05 compared to 6 months). At 6 months and 2 years, the observed residual stromal bed (RSB) was 30 microns thicker than the RSB calculated by the Ziemer LDV Z8 software 2022. The difference between predicted (POZ) and effective (EOZ) optical zone correlated with the degree of myopia corrected (r = 0.6, p < 0.001). The difference between POZ and EOZ inversely correlated with astigmatic correction (r = −0.5, p < 0.001). Conclusions: In patients with high myopia, CLEAR showed good predictability and efficacy. Both UDVA and SE improved during the first 6 months, and remained stable at 2 years. The effective RSB was thicker than expected, and patients with high astigmatism achieved a larger EOZ.